Vitamin D and other environmental risk factors in Colombian patients with multiple sclerosis (2020)
Epstein-Barr virus (EBV) seropositivity and smoking history in a Colombian population. Methods: We conducted a cross-sectional study between 2017 and 2018. We measured vitamin D levels and EBV antibody titers and administered a questionnaire to assess dietary habits, smoking, second-hand smoking and duration of smoking, sunlight exposure, physical activity, and personal and family history in individuals with and without multiple sclerosis during adolescence. A multivariable logistic regression model was then performed to explore the association between vitamin D status and MS. Results: : A total of 87 individuals with MS (mean age 40.9 years; 65.52% females) and 87 without MS (mean age 55 years; 65.52% females) were included in the analysis. In the multivariable analysis, after controlling for supplementation vitamin D levels did not differ between both groups and no difference was found regarding tobacco smoke exposure. The proportion of individuals who tested positive for anti-EBV nuclear antigen was significantly higher in individuals with MS (95.4% vs 82.76%, p = 0.028) Conclusion: We did not find a statistically significant association between MS and vitamin D levels while antiEBV nuclear antigen titers behaved as previously described in the literature. This study provides new evidence of the association between MS and different risk factors in our country, reinforcing the hypothesis that the pathogenesis of MS is multifactorial. Further studies are needed to better define the association between environmental factors and the development of MS in low prevalence areas.